(untitled) (Annals of Medical Research, 2021)
Aim: Recently, one of the most preferred options in the surgical treatment of obesity is laparoscopic sleeve gastrectomy The purpose of this study is to investigate the incidence of port site hernia formation and the factors affecting the fascia defect in the group with and without closure after LSG.Material and Methods: The data of patients who were operated due to morbid obesity in a single center between March 2014 and June 2018 was reviewed and analyzed retrospectively. The patients were divided into two groups, being those in whom the fascial defect at the 12-mm trocar insertion site from which the gastric remnant was removed during surgery was closed, and those in whom the fascial defect was not closed. The incidence of port site hernia and the factors affecting the development of port site hernia were evaluated with physical and ultrasound examinations 1year after surgery.Results: The study was completed with a total of 207 patients, of which 112 fascias was not closed and 95 fascia was closed. The rate of hernia formation was significantly lower in the fascial closure group than in the non-fascial closure group (p:0,036). Aside from this parameter, no significant difference was identified in the other parameters of the two groups. Age was significantly higher in patients that developed hernias following surgery than in those who did not develop hernias.Conclusion: This study determined that the closure of the fascial defect is a protective factor against the development of port site hernia when compared to non-fascial closure.